The contact of Slavic languages and French: towards an adapted typology of interference - Rackova, Lucia (Romanica Olomucensia, 2017)
The paper deals with grammatical interference in the formation of the passive voice in French by Slavic native speakers. In Slavic languages, which are mostly of a flexive type, the passive voice holds a particular position. The specificity of its use lies in the lower frequency of the passive in comparison with the active voice, as well as in a different degree of variability of passive structures. How can these specificities lead to negative transfer in the utterances of Slavic native speakers in French? The study is a contribution to the verification of the hypothesis on the correlation between the typology of languages in contact and the typology of forms of linguistic interference, putting forward arguments in favour of a possible adaptation of the grammatical interference typology of Weinreich in a particular linguistic context.
Keywords: French language; Slavic languages; grammatical interference; language contact; passive voice